Tuberculous Meningitis in Adults: A Review of 160 Cases. (24th April 2012) - Pehlivanoglu, Filiz; Kart Yasar, Kadriye; Sengoz, Gonul
Abstract : Objective . This study aimed to evaluate epidemiological, clinical, laboratory, and neuroimaging features of 160 adult patients with tuberculous meningitis (TBM) according to "Thwaites' diagnostic index." Methods . The subjects of this retrospective study are the patients with TBM who were followed up between years 1998 and 2009 in a tertiary referral hospital. Diagnosis of TBM was based on clinical, laboratory, and neuroimaging signs and Thwaites' diagnostic index. Results . Mycobacterium tuberculosis was isolated from CSF in 59 of 148 patients. Seventeen percent of the patients died, 71% recovered completely, and 13% recovered with neurological sequel at the end of the sixth month. Conclusions . Despite new developments in laboratory or neuroimaging techniques, the diagnosis of TBM is still based on clinical features with the help of laboratory. Early diagnosis by suspecting TBM may prevent therapy delay and may result in decrease in the mortality and morbidity.